Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

The structure and subduction relicts of the Changchun–Yanji suture, NE China: new evidence from deep seismic reflection profiling - Jiaduo Zhang; Hesheng Hou; Jianbo Zhou; Wei Fu; Rui Guo; Zongdong Pan; Hengcheng Ying (International Journal of Earth Sciences, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Distribution Analysis of Local Ice Pressures in the Indentation Test at Various Velocities - Guojun Wang; Qianjin Yue; Dayong Zhang; Yanghua Fu; Xin Peng; Rui Dong (Journal of Marine Science and Engineering, 2022)
When sea ice acts on vertical structures, there are much higher pressures in localized areas known as high-pressure zones (HPZs) than in other areas. The damage failure mode of sea ice varies with the sea ice velocity and affects the distribution of HPZs. In this study, an indentation test that drives ice sheet interaction with a vertical rigid plate (indentor) was designed, and a pressure sensor (consisting of 32 × 32 small pressure units of 100 mm2) was installed on the indentor face to measure the local ice pressure (LIP) at various velocities. The distribution of the LIPs along the ice thickness, the probability distribution of the LIPs and the distribution relationship of the LIPS in space and time were obtained from the measurement. The results show that the LIPs were mainly distributed in the middle of the sea ice, which is consistent with full-scale observations and previous research. Ductile failure of the sea ice results in a larger LIP distribution area than brittle failure at the same threshold kt (kt = σL/σcr). The probability distribution of the LIPs decreases exponentially with increasing pressure and follows a lognormal distribution. The maximum LIP appears at the peak moment of the global force when the sea ice failure mode is mainly ductile failure. However, the maximum LIP may not occur at the peak moment when the sea ice failure is mainly brittle failure and, instead can appear at any moment in the global force time history curve. The HPZ (which is larger than 7/8 times the maximum LIP) area is less than 2% of the nominal contact area at various velocities. The influence of the sea ice velocity on the spatial and temporal distribution of LIP is analyzed, and the results provide a reference for designing structures with local strength in ice regions.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)